Toward a New School Science Program. - Munson, Howard R. (Elementary School Journal, 1958)
The article discusses the development of a new science program in elementary schools in the U.S. Key issues examined include an increase in the consciousness of Americans towards science courses, a comparison of the science curricula of American and Russian schools and the issues' implications for science education.